2016
DOI: 10.3892/ijmm.2016.2685
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 4 inhibits breast cancer cell growth through the upregulation of PDCD4

Abstract: Breast cancer is a common malignant tumor affecting women. The study of the association between breast cancer and molecular aberrations may lead to the development of novel diagnostic and therapeutic strategies for the disease. In the present study, we examined the role of ubiquitin-specific protease 4 (USP4) in breast cancer. We found that USP4 expression was significantly decreased in breast cancer tissue samples compared with paired normal breast tissue samples (P<0.001). USP4 was identified as a tumor supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…a and b ). In contrast, a recent study suggested that USP4 also exhibits an oncosuppressive property by targeting programmed cell death 4 (PCD4), consistent with the results obtained in some other cancer types . Thus, these results, together with our observation, imply a divergent role of USP4 in breast cancer progression.…”
Section: Discussionsupporting
confidence: 91%
“…a and b ). In contrast, a recent study suggested that USP4 also exhibits an oncosuppressive property by targeting programmed cell death 4 (PCD4), consistent with the results obtained in some other cancer types . Thus, these results, together with our observation, imply a divergent role of USP4 in breast cancer progression.…”
Section: Discussionsupporting
confidence: 91%
“…These studies demonstrate USP4 as a powerful tumour promoter and an important determinant for canonical oncogenic signalling. However, in breast cancer, USP4 was also recognized as a tumour suppressor for its up‐regulatory effect on programmed cell death 4 (PDCD4) to restrain tumour growth 20. Moreover, USP4 was able to target TRAF2 and TRAF6 for deubiquitination and thereafter inhibited TNFα‐induced cancer cell migration 34.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the elevated USP4 expression contributed to the growth of colorectal cancer via deubiquitination and stabilization of oncogene PRL‐3 19. On the other hand, USP4 could also exert its tumour‐suppressive role through inhibiting cell proliferation or promoting cell apoptosis in breast cancer and neck squamous cell carcinoma 20, 21. These results suggested that the impact of USP4 on cancer biology is tumour‐type specific and tissue‐context dependent.…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, SRSF3 was also reported to modulate the expression of PDCD4 gene through the alternative splicing and translational mechanisms [111]. PDCD4 reportedly acted the tumor suppressor in repressing the transformation and immortality of cancer cells [113]. SRSF3 silencing was noted to reduce the relative level of PDCD4 isoform 2, containing the partial PDCD4 intron 3 in distinct cancer cells.…”
Section: Impacts Of Alternative Splicing Events On Apoptosismentioning
confidence: 99%